2022
DOI: 10.12806/v21/i1/r2
|View full text |Cite
|
Sign up to set email alerts
|

AVATARS MEET FACE-TO-FACE: Learning Leadership Online: A Thematic Analysis of East-African Perspectives

Lorraine Ann,
Zahra Aziz

Abstract: It can be difficult for students to digest and learn complex theories of organizational culture and change without being able apply the steps to a real or imagined scenario. Oftentimes, they lack experience and can't imagine the components of each phase or step without a practical example. This article discusses the theoretical background of leading positive organizational change and then uses a case study to help students apply their knowledge. It highlights the fictional leadership dilemma of a young Army of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For this work, we engaged in a review of articles published in the Journal of Leadership Education since its founding that intersected with online leadership education-12 articles emerged, and the pieces highlighted below are aligned with our positionalities as educators. In two of these articles, Manning-Ouellette and Black (2017) and Ann and Aziz (2022) compared online leadership education with in-person (i.e., face-to-face (F2F)) leadership education. Specifically, Manning-Ouellette and Black conducted a directed content analysis of 53 students' assignments to explore differences in student learning in the online and F2F class environments.…”
Section: Reflecting Back: Jole and Online Leadership Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…For this work, we engaged in a review of articles published in the Journal of Leadership Education since its founding that intersected with online leadership education-12 articles emerged, and the pieces highlighted below are aligned with our positionalities as educators. In two of these articles, Manning-Ouellette and Black (2017) and Ann and Aziz (2022) compared online leadership education with in-person (i.e., face-to-face (F2F)) leadership education. Specifically, Manning-Ouellette and Black conducted a directed content analysis of 53 students' assignments to explore differences in student learning in the online and F2F class environments.…”
Section: Reflecting Back: Jole and Online Leadership Educationmentioning
confidence: 99%
“…However-as COVID-19 so clearly illustrated-students still face significant challenges in online learning given the very real digital divide that creates inequity and potential dehumanization (Richards et al, 2021). In their Kenya-based study, Ann and Aziz (2022) found that students faced accessibility issues in their online classes due to a lack of reliable internet connection and affordable devices. Students in the United States have encountered similar accessibility issues (Means & Neisler, 2021;Mize & Glover, 2021).…”
Section: Reflecting Back: Jole and Online Leadership Educationmentioning
confidence: 99%
See 1 more Smart Citation